Accounting Conservatism And Its Influence On The Value Of Corporate Social And Environmental Investment - Simon O. ILOGHO; Uwalomwa UWUIGBE; Olayinka AKINLO; Olubukola R. UWUIGBE; Ijachi O. IJACHI; Busola E. KEHINDE (Communications of International Proceedings, 2021)
There have been conflicting results in prior empirical studies concerning the value corporate social and environmental activities add to firms and these results are caused by several influential factors. This study examines one of these factors, which is the level of conservatism of firms. Accounting conservatism, because of its application in the treatment of potential profit and potential losses would affect the way strategic investments are recognised. These strategic investments (social and environmental investments) would be captured as losses in a short-term period (less than 5 years) and this would affect the outcome of the result by these empirical studies. This study reviewed fifty prior empirical works from top journals from 1998-2020 examining their results and the firm-year coverage of their data using descriptive analysis. Findings revealed that studies that show a positive relationship between corporate social and environmental performance and firm performance cover an average of 7 firm years (above five years). Studies that show a negative relationship between corporate social and environmental performance and firm performance cover an average of 4.5 firm years (below five years). These descriptive results reveal that empirical studies show a negative relationship between these two variables because they cover a short time frame and as a result returns social and environmental (strategic) investment cannot be realised due to the level of firm conservatism. However, studies that extend their time frame beyond the strategic five years can obtain positive results because returns from social and environmental (strategic) investment can easily be realised.
Keywords: Corporate social responsibility; Environmental accounting; Social accounting; Accounting conservatism; Firm value.